PENGARUH MODEL REALISTIC MATHEMATIC EDUCATION (RME) BERBASIS ETNOMATEMATIC TERHADAP HASIL BELAJAR SISWA KELAS IV SD NEGERI 101953 PANTAI CERMIN - Nuraminah; Ahmad Landong (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there are differences and how the mathematics learning outcomes of grade IV elementary school students using the RME learning model are compared to students who use direct learning. This study was conducted at SD Negeri 101953 Pantai Cermin. This study is a Quisi Experiment study, sampling was carried out by purposive sampling. The researcher used one class, namely the experimental class in grade IV elementary school with 21 students consisting of 12 girls and 9 boys. The instrument used to measure the understanding of the concept of triangle geometry. Based on research conducted in the class of SD Negeri 101953 Pantai Cermin, it shows that there is a significant influence of the use of the Realistic Mathematics Education (RME) learning model on the mastery of Mathematics learning outcomes of grade IV students of SD Pantai Cermin. It can be seen from the pre-test and post-test scores, it is known that the T count is 11,741 where the T count is greater than the T table of 11,741 or 11,741> 0.456. In addition, it can be seen that the sig level is 0.006 where in this case the sig value. smaller than 0.05 or 0.000 < 0.05 then the Realistic Mathematics Education (RME) learning model based on ethnomathematics has an effect on the mathematics learning outcomes of grade IV students of SD Negeri 101953 Pantai Cermin.